1999
DOI: 10.1093/emboj/18.10.2683
|View full text |Cite
|
Sign up to set email alerts
|

Strong host resistance targeted against a viral suppressor of the plant gene silencing defence mechanism

Abstract: The 2b protein encoded by cucumber mosaic cucumovirus (Cmv2b) acts as an important virulence determinant by suppressing post-transcriptional gene silencing (PTGS), a natural plant defence mechanism against viruses. We report here that the tomato aspermy cucumovirus 2b protein (Tav2b), when expressed from the unrelated tobacco mosaic tobamovirus (TMV) RNA genome, activates strong host resistance responses to TMV in tobacco which are typical of the gene-for-gene disease resistance mechanism. Domain swapping betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(123 citation statements)
references
References 71 publications
3
112
0
4
Order By: Relevance
“…Total plant RNA extraction and RNA gel blotting analysis were performed as described previously (Li et al, 1999). Hybridization probes were labeled with 32 P using the Amersham Megaprime DNA labeling kit (Piscataway, NJ).…”
Section: Dna and Rna Analysesmentioning
confidence: 99%
“…Total plant RNA extraction and RNA gel blotting analysis were performed as described previously (Li et al, 1999). Hybridization probes were labeled with 32 P using the Amersham Megaprime DNA labeling kit (Piscataway, NJ).…”
Section: Dna and Rna Analysesmentioning
confidence: 99%
“…N-terminal region of 1a protein contains putative methyltransferase domain [39] and C-terminal region shows sequence similarity to viral helicases [16]. RNA 2 encodes for another protein 2b, which is expressed from the subgenomic RNA 4A and acts as suppressor of gene silencing [4,5,27]; plays a role in long distance movement of the virus [9,23,43,54] and also behave as pathogenicity determinant [10,41,43]. A recent finding suggested that this suppressor protein is indirectly involved in aphid transmission [56].…”
Section: Introductionmentioning
confidence: 99%
“…In one case, an RNA sequence was also shown to act as an Avr factor (Szittya & Burgyan, 2001). Some of these Avr determinants have been reported to function as pathogenic determinants; for instance, turnip crinkle virus CP (Ren et al, 2000;Qu et al, 2003), cucumovirus 2b protein (Li et al, 1999), cauliflower mosaic virus transactivator/viroplasmin protein (Kobayashi & Hohn, 2004) and potyvirus P3 protein (Johansen et al, 2001;Jenner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%